POTENSI Trichoderma asperellum TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KEDELAI TERINFEKSI SOYBEAN MOSAIC VIRUS - Nisa, Indah Hafidhotun; Lamdo, Herfandi; Yanto, Yanto (Universitas Lampung, 2025)
Soybean Mosaic Virus (SMV) is a species in the Potyvirus genus, which is a plant RNA virus known to attack important agricultural crops. Infection by SMV during early growth can reduce productivity by 25.48% to 93.84% in soybean plants. Trichoderma plays a role through the contact of spores on root surfaces, leading to the production of plant defenses such as peptides and proteins, and assisting in nutrient absorption, thereby allowing Trichoderma to control pathogen growth and enhance plant growth and yield. This research aims to determine the effect of Trichoderma asperellum doses on the growth and yield of soybean plants infected with Soybean Mosaic Virus. The study was conducted from June to September 2024 using an experimental method with a randomized block design consisting of 4 replications and 6 treatment levels: T0 = 0 ml (control), T1 = 10 ml, T2 = 20 ml, T3 = 30 ml, T4 = 40 ml, T5 = 50 ml per plant with each 1 ml containing spore count of T. asperellum = 46.5 x 102 spores). The results showed that the dose of Trichoderma asperellum had a real effect on the growth and yield of soybean plants infected with Soybean Mosaic Virus. The application of Trichoderma asperellum was able to increase plant height by 36.33%, the number of leaves by 42.36%, the wet weight of the plant by 48.97%, the dry weight of the plant by 48.03%, the dry weight of the roots by 64.43%, and the number of pods by 34.26% in soybean plants compared to no application of Trichoderma asperellum. Administration of Trichoderma asperellum 50 ml dose obtained the best growth and results.